Technics and Time 2 Disorientation - Stiegler, Bernard 1952-2020 (Stanford, CA Stanford University Press, 2009)
"Disorientation" is the first publication in English of the second volume of "Technics and Time", in which French philosopher Bernard Stiegler engages in a close dialogue with Husserl, Derrida, and other philosophers who have devoted their energies to technics, such as Heidegger and Simondon. The author's broad intent is to respond to Western philosophy's historical exclusion of technics and techniques from its metaphysical questionings, and in so doing to rescue critical and philosophical thinking. For many years, Stiegler has explored the origins and philosophical, ethical, and political stakes of a global process he calls "the industrial temporalization of consciousness."Here, demonstrating that technology - including alphabetical writing - is memory, he argues that through new technologies of retention and inscription we have come to live in a world where time devours space, a disoriented world in which we have lost our bearings. Immersed in the multimedia of an over-connected world, with time and space as we know them abolished, we no longer find 'cardinal points' to guide us and may even be led where we do not wish to go. We must therefore prepare to confront new spheres of ideological control and discover new possibilities in the digital environment.
Keywords: Philosophy; Technology